2005
DOI: 10.1016/j.freeradbiomed.2004.10.031
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxynonenal increases γ-glutamyl transpeptidase gene expression through mitogen-activated protein kinase pathways

Abstract: Abstractγ-Glutamyl transpeptidase (GGT) plays key roles in the metabolism of glutathione. Previous studies have shown that GGT expression was increased by oxidants, but the mechanism remains unclear. In the present study, the effects of 4-hydroxy-2-nonenal (HNE), an electrophilic end product of lipid peroxidation, on GGT expression were investigated in rat lung epithelial type II (L2) cells. We demonstrated that HNE increased GGT activity and mRNA content in both time-and dose-dependent manners. Actinomycin D,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 75 publications
(77 reference statements)
3
37
0
Order By: Relevance
“…An example of this is the signaling pathways involved in the EpRE-mediated NQO-1 and GCL induction in HepG2 cells; protein kinase C (PKC) and ERK/p38MAPK were involved, respectively in their EpRE activation [66,69]. As to the signaling pathways responsible for GGT induction by HNE, recent studies from our laboratory suggest that ERK1/2 and P38MAPK mediate the induction of GGT mRNA V-2 through regulation of the activation of Nrf2 [31,87]. The present study, however, focused on the identification of the cis element regulating GGT V2 expression, verifying whether it was the element to which Nrf2 bound and the tissue distribution of GGT V2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of this is the signaling pathways involved in the EpRE-mediated NQO-1 and GCL induction in HepG2 cells; protein kinase C (PKC) and ERK/p38MAPK were involved, respectively in their EpRE activation [66,69]. As to the signaling pathways responsible for GGT induction by HNE, recent studies from our laboratory suggest that ERK1/2 and P38MAPK mediate the induction of GGT mRNA V-2 through regulation of the activation of Nrf2 [31,87]. The present study, however, focused on the identification of the cis element regulating GGT V2 expression, verifying whether it was the element to which Nrf2 bound and the tissue distribution of GGT V2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have demonstrated that GGT gene expression was increased by HNE in L2 cells, and GGT mRNA V-2 was the major type of GGT mRNA being induced [31]. To further examine the mechanism of GGT mRNA V-2 induction by HNE, we first determined its expression pattern in response to HNE.…”
Section: Increase Of Ggt Mrna V-2 By Hne In L2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that physiological concentrations of HNE can stimulate cellular proliferation (187)(188)(189), differentiation (190,191), and cytoprotective response (181,(192)(193)(194)(195)(196)(197), through affecting multiple signaling pathways. As low as 0.5 μM, HNE can induce transcription of glutamate cysteine ligase, the first enzyme of GSH synthesis, through activation of the Nrf2-EpRE signaling pathways (198).…”
Section: Signaling Pathways Activated By Hnementioning
confidence: 99%
“…Regarding p38MAPK, Kumagai et al reported that both p38MAPK and its upstream kinase MKK3/6, were phosphorylated (activated) upon exposure to 25 μM HNE (210). Other researchers also noticed that HNE could markedly increase p38MAPK phosphorylation (196,213). These suggest that HNE activate p38MAPK through targeting upstream signaling molecules, which again have not yet been identified.…”
Section: B Mapk Activation By Hnementioning
confidence: 99%